Acute toxicities after proton beam therapy following breast‐conserving surgery for breast cancer: Multi‐institutional prospective PCG registry analysis. Issue 9 (15th April 2020) - Thorpe, Cameron S.; Niska, Joshua R.; Anderson, Justin D.; Girardo, Marlene E.; McGee, Lisa A.; Hartsell, William F.; Larson, Gary L.; Tsai, Henry K.; Rossi, Carl J.; Rosen, Lane R.; Vargas, Carlos E.
Abstract: We investigated adverse events (AEs) and clinical outcomes for proton beam therapy (PBT) after breast‐conserving surgery (BCS) for breast cancer. From 2012 to 2016, 82 patients received PBT in the prospective multi‐institutional Proton Collaborative Group registry. AEs were recorded prospectively at each institution. Median follow‐up was 8.1 months. Median dose was 50.4 Gy in 28 fractions. Most patients received a lumpectomy bed boost (90%) and regional nodal irradiation (RNI)(83%). Six patients (7.3%) experienced grade 3 AEs (5 with dermatitis, 5 with breast pain). Body mass index (BMI) was associated with grade 3 dermatitis ( P = .015). Fifty‐eight patients (70.7%) experienced grade ≥2 dermatitis. PBT including RNI after BCS is well‐tolerated. Elevated BMI is associated with grade 3 dermatitis.